The Effect of Teaching Based on the ASPIRE Model on the Acquisition of Algebraic Concepts among 10th Grade Students with Different Mathematical Self-Concept - Al Abed , Adnan; Al Baba, Mohammed (Dirasat: Educational Sciences, 2023)
Objectives: This study aimed to investigate the effect of teaching based on the ASPIRE model on the acquisition of algebraic concepts among 10th grade students with different mathematical self-concepts. Methods: The study employed an experimental method using a quasi-experimental design. The study subjects were selected from two schools in the capital city, Amman, Jordan. Two classes were randomly assigned in each school, with the experimental group consisting of 60 students and the control group consisting of 55 students. The teaching material was prepared according to the teaching model, an algebraic concepts acquisition test was developed, and a mathematical self-concept scale was utilized. Results: The results showed statistically significant differences (α = 0.05) in the acquisition of algebraic concepts attributed to the teaching method, favoring the experimental group. However, there were no statistically significant differences (α = 0.05) in the acquisition of algebraic concepts due to the interaction between the teaching method and mathematical self-concept. Conclusions: This study suggests urging mathematics teachers to adopt teaching topics in mathematics based on the dimensions of the ASPIRE model. Additionally, it recommends conducting introductory workshops for teachers on the ASPIRE model and training them to build teaching models based on it.